Cytological characterization of an Aspergillus nidulans mutant from a strain with chromosomic duplication - Giancoli,Ágata Cristiane Huppert (2010)
A development mutant, named V103, was obtained spontaneously from the A strain of A. nidulans. The A strain contains a duplicated segment of chromosome I that has undergone translocation to chromosome II (I → II). It is mitotically unstable and generates phenotypically deteriorated types, some with enhanced stability. The deteriorated variants of A. nidulans show abnormal development, exhibiting slower colony growth, variations in colony pigmentation and changes in conidiophore structure. The alterations observed in the conidiophore include fewer metulae and phialides, further elongation and ramification of these structures, delayed nuclear migration and the presence of secondary conidiophores.